Clinical Laboratory and Epidemiological Features of Sudden Exanthema in Children Saint-Petersburg - E. V. Sharipova; I. V. Babachenko; Yu. I. Sichkovskaja; Yu. Yu. Chernyshova (LLC "Diagnostics and Vaccines", 2016)
The paper studies the clinical and epidemiological features of one of the acute clinical forms of infection caused by the human herpes virus type 6 - «sudden exanthema » - in children of St. Petersburg. The study involved 149 children hospitalized aged 6 months to 15 years in the period from 2012 to 2014. Sudden rash confirmed by molecular genetic studies in 38 children. The disease is mainly observed in patients of the first two years of life. Rash and toxic syndromes dominated in clinical picture.